The Role of Endothelin and Endothelin Antagonists in Chronic Kidney Disease - Raina, Rupesh (Kidney Dis (Basel), 2020)
BACKGROUND: Endothelins (ET) are a family of peptides that act as potent vasoconstrictors and pro-fibrotic growth factors. ET-1 is integral to renal and cardiovascular pathophysiology and exerts effects via autocrine, paracrine and endocrine signaling pathways tied to regulation of aldosterone, catecholamines, and angiotensin. In the kidney, ET-1 is critical to maintaining renal perfusion and controls glomerular arteriole tone and hemodynamics. It is hypothesized that ET-1 influences the progression of chronic kidney disease (CKD), and the objective of this review is to discuss the pathophysiology, and role of ET and endothelin receptor antagonists (ERAs) in CKD. SUMMARY: The use of ERAs in hypertensive nephropathy has the potential to decrease proteinuria, and in diabetic nephropathy has the potential to restore glycocalyx thickness, also decreasing proteinuria. Focal segmental glomerular sclerosis has no specific Food and Drug Administration-approved therapy currently, however, ERAs show promise in decreasing proteinuria and slowing tissue damage. ET-1 is a potential biomarker for autosomal dominant polycystic kidney disease progression and so it is thought that ERAs may be of some therapeutic benefit. KEY MESSAGES: Multiple studies have shown the utility of ERAs in CKD. These agents have shown to reduce blood pressure, proteinuria, and arterial stiffness. However, more clinical trials are needed, and the results of active or recently concluded studies are eagerly awaited.